Sintering behaviour and microwave dielectric properties of BaAl2−2x(ZnSi)xSi2O8 ceramics. Issue 4 (April 2018) - Song, Xiao-Qiang; Lu, Wen-Zhong; Wang, Xiao-Chuan; Wang, Xiao-Hong; Fan, Gui-Fen; Muhammad, Raz; Lei, Wen
Abstract: BaAl2−2 x (ZnSi) x Si2 O8 ( x  = 0.2–1.0) ceramics were prepared using the conventional solid-state reaction method. The sintering behaviour, phase composition and microwave dielectric properties of the prepared compositions were then investigated. All compositions showed a single phase except for x  = 0.8. By substituting (Zn0.5 Si0.5 ) 3+ for Al 3+ ions, the optimal sintering temperatures of the compositions decreased from 1475 °C ( x  = 0) to 1000 °C ( x  = 0.8), which then slightly increased to 1100 °C ( x  = 1.0). Moreover, the phase stability of BaAl2 Si2 O8 was improved. A novel BaZnSi3 O8 microwave dielectric ceramic was obtained at the sintering temperature of 1100 °C. This ceramic possesses good microwave dielectric properties with ε r  = 6.60, Q  ×  f  = 52401 GHz (at 15.4 GHz) and τ f  = −24.5 ppm/°C.